2018
DOI: 10.3389/fimmu.2018.02188
|View full text |Cite
|
Sign up to set email alerts
|

From Inflammasome to Exosome—Does Extracellular Vesicle Secretion Constitute an Inflammasome-Dependent Immune Response?

Abstract: Inflammasomes are intracellular protein complexes of pattern recognition receptors and caspase-1, with essential functions in regulating inflammatory responses of macrophages and dendritic cells. The primary role of inflammasomes is to catalyze processing and secretion of pro-inflammatory cytokines IL-1β and IL-18. Recently, intracellular non-canonical inflammasome activation by caspases-4/5, which are also regulators of pyroptosis via processing gasdermin D, has been elucidated. Caspase-1, the effector protea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 78 publications
0
81
0
Order By: Relevance
“…They are the products of exocytosis; they contain DNA, coding or noncoding RNAs (ncRNAs), and protein fragments that are secreted by their parental cell and can be taken into the recipient cells. Exosomes are reported 2 BioMed Research International to carry out several physiological and pathophysiological functions during carcinogenesis and immunomodulation in both in vitro and in vivo conditions [12][13][14][15]. ncRNAs of the exosomes have been proved to play an important role in regulation of these procedures [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are the products of exocytosis; they contain DNA, coding or noncoding RNAs (ncRNAs), and protein fragments that are secreted by their parental cell and can be taken into the recipient cells. Exosomes are reported 2 BioMed Research International to carry out several physiological and pathophysiological functions during carcinogenesis and immunomodulation in both in vitro and in vivo conditions [12][13][14][15]. ncRNAs of the exosomes have been proved to play an important role in regulation of these procedures [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes are reported 2 BioMed Research International to carry out several physiological and pathophysiological functions during carcinogenesis and immunomodulation in both in vitro and in vivo conditions [12][13][14][15]. ncRNAs of the exosomes have been proved to play an important role in regulation of these procedures [14,15]. Danesh et al in their study have revealed that exosomes derived from RBC units could potentiate T-cell survival and mitogen-induced proliferation through antigen presenting cells (APCs), eventually contributing to TRIM [9].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammaging is also characterized by release of microvesicles and exosomes from stressed or damaged cells [111]. These small circular membrane fragments that contain cell cytoplasma-derived mRNA, microRNA and proteins may be of diagnostic value [112,113].…”
Section: Circulating Exosomal Micrornasmentioning
confidence: 99%
“…However, recent work suggests that increased NLR Family Pyrin Domain Containing 3 (NLRP3) inflammasome activity, which plays a key role in innate immunity, can regulate EV secretion, with several reports demonstrating direct associations between NLRP3 inflammasome activation and enhanced exosome release rates and changes in exosome cargo compositions. 72 NLRP3 inflammasome polymorphisms are also associated with the development of certain cancers, including breast cancer, melanoma, and hepatocellular carcinoma (HCC), 73 and NLRP3 inflammasome inhibitors have been patented for potential cancer therapeutic applications. 74 The NLRP3 inflammasome is a multi-subunit cytosolic protein complexes that assembles upon exposure of its pattern recognition receptor, NLRP3, to a broad range of damage-associated molecular patterns or responses induced by them, including extracellular adenosine triphosphate (ATP), crystalline complexes and protein aggregates, mitochondrial dysfunction and lysosomal damage.…”
Section: Inflammationmentioning
confidence: 99%
“…Multiple studies have examined TDE effects on tumor development and tumor microenvironment inflammation, as described in the following sections, but relatively few have examined how stress and proinflammatory tumor cell responses influence exosome secretion. However, recent work suggests that increased NLR Family Pyrin Domain Containing 3 (NLRP3) inflammasome activity, which plays a key role in innate immunity, can regulate EV secretion, with several reports demonstrating direct associations between NLRP3 inflammasome activation and enhanced exosome release rates and changes in exosome cargo compositions . NLRP3 inflammasome polymorphisms are also associated with the development of certain cancers, including breast cancer, melanoma, and hepatocellular carcinoma (HCC), and NLRP3 inflammasome inhibitors have been patented for potential cancer therapeutic applications …”
Section: Introductionmentioning
confidence: 99%